MiR-124-3p Suppresses the Dysfunction of High Glucose-Stimulated Endothelial Cells by Targeting G3BP2 - Zhao, Haijun; He, Yanhui (Frontiers in Genetics, 2021)
Background: Diabetic retinopathy (DR) is the most important manifestation of diabetic microangiopathy. MicroRNAs (miRNAs), members of noncoding RNAs, have been frequently reported to regulate various diseases including DR. MiR-124-3p is involved in DR based on bioinformatics. The current study aimed to investigate the role of miR-124-3p in high glucose (HG)-treated human retinal microvascular endothelial cells (HRMECs), an in vitro model of DR. Methods: Bioinformatics analysis was applied to reveal the targets downstream miR-124-3p. A series of assays including CCK-8, luciferase reporter, western blot, and tube formation assays were used to explore the function and mechanism of miR-124-3p in HG-stimulated HRMECs. Results: We found out that miR-124-3p was downregulated in HG-stimulated HRMECs. Functionally, miR-124-3p overexpression restrained the HG-induced cell injury of HRMECs. Mechanistically, we predicted 5 potential target mRNAs of miR-124-3p. G3BP stress granule assembly factor 2 (G3BP2) was validated to bind with miR-124-3p. Rescue assays showed that miR-124-3p suppressed cell injury of HG-stimulated HRMECs through G3BP2. In addition, miR-124-3p regulated the p38MAPK signaling pathway by G3BP2, and G3BP2 promoted injury of HG-treated HRMECs through the activation of the p38MAPK signaling pathway. Conclusions: MiR-124-3p suppressed the dysfunctions of HG-treated HRMECs by targeting G3BP2 and activating the p38MAPK signaling. This new discovery provided a potential biomarker for DR treatment.